The orientation setting of buildings in the traditional Malay settlement: a case study of Kg Seri Tanjung, Sungai Udang, Melaka - N Murtaza, Fatin Farhana; Ibrahim, Illyani; Abdullah, Alias (Malaysian Institute Of Planners, 2020)
The orientation of buildings is one of the factors that define the characteristics and pattern of a settlement. The purpose of this paper is to analyse the orientation setting of the buildings in one of the gazetted traditional Malay settlements in Melaka, namely Kg Seri Tanjung, which has been listed as Heritage Village in Melaka State Structure Plan 2035. The objective of this research is to identify the orientation setting of the built-up areas and analyse the factors of the orientation of the built up. This research has used the drone technology to identify the orientation setting of each built up in the settlements, which is also supported by the ground survey to confirm the social interactions among the settlers. The findings indicate that the orientation of a building is influenced by the geographical factors and distribution of houses that depends on the family ties among the dwellers. It is identified that the geographical factors and relationship among the neighbours are highly related to the orientation of the buildings, which is also contributed by the factors of orientation of the buildings towards the natural environment, road, qiblat and its adjacent buildings. This analysis highlights and acknowledges some potential values in the traditional Malay settlement settings that can be used as a reference for the preservation of the characters of the future traditional settlement. The findings of this study are also a part of the urban design principles of the traditional Malay settlement that is important to preserve the identity of Malay in future development.